Comparative analysis of four early white, seedless table grape cultivars in the Orange River area - Burger, Henning (Henning Jacobus),1978- (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- University of Stellenbosch, 2002.